Anti-Alzheimers activity and molecular mechanism of albumin-derived peptides against AChE and BChE. Issue 2 (24th January 2018) - Yu, Zhipeng; Wu, Sijia; Zhao, Wenzhu; Ding, Long; Fan, Yue; Shiuan, David; Liu, Jingbo; Chen, Feng
Abstract : Alzheimer's disease (AD) is a global health issue affecting millions of elderly people worldwide. Abstract : Alzheimer's disease (AD) is a global health issue affecting millions of elderly people worldwide. The aim of the present study was to identify novel anti-AD peptides isolated from albumin. Anti-AD activities of the peptides were evaluated via inhibitory activities on acetylcholinesterase (AChE) and butyrylcholinesterase (BChE). Furthermore, the potential molecular mechanisms of the KLPGF/AChE were investigated by CDOCKER of Discovery studio 2017. The results revealed that peptide KLPGF could effectively inhibit AChE with an inhibition rate of 61.23% at a concentration of 50 μg mL −1 . In addition, the peptide KLPGF came in contact with acylation sites and peripheral anion sites of AChE. The present study demonstrates that the peptide KLPGF could become a potential functional food intervention in AD.